Destructive bone lesions in primary amyloidosis. Issue 733 (November 1986) - Kramer, M. R.; van Dijk, J. M.; Hadas, I.; Hershko, C.
Abstract : We describe a patient with primary amyloidosis in whom multiple osteolytic lesions caused by amyloid bone tumours developed, and review the clinical features of the 18 cases with primary amyloidosis in whom destructive bone lesions have been reported. In contrast to amyloidosis associated with multiple myeloma, destructive lesions in the primary disease are mainly located to long bones; joint involvement is common, and radionuclide bone scan shows pronounced uptake of 99mTc-PP by the destructive bone lesions. Despite the superficial similarity between the destructive bone lesions associated with primary amyloidosis and multiple myeloma, distinction between these entities on clinical grounds is possible and may be easily confirmed by direct aspiration of the osteolytic infiltrates.